Role of rare-earth (Eu, DY and Yb) substitution on determining the structural, thermal and superconducting properties of BSCCO superconductor prepared via coprecipitation method / Siti Hawa Jamil - Jamil, Siti Hawa (2015)
In this study, the Bi1.6Pb0.4Sr2Ca2-xRExCu3Oy (RE = Eu, Dy and Vb) where x = 0.000, 0.025, 0.050, 0.100 and 0.200 which were synthesised through the coprecipitation (COP) method was successfully prepared. The phase purity and structural properties were performed by X-ray Diffractometer (XRD), Field-Emission Scanning Electron Microscopy (FESEM) and Energy Dispersive X-ray Spectroscopy (EDX). Meanwhile, the powders at each stage of the coprecipitated powder, precalcined and calcined products were characterized by Thermogravimetric Analysis (TOA) and Fourier Transform Infrared Spectroscopy (FTIR). Furthermore, the resistivity and critical current density were measured by using the four-point probe method. The Bi-2223 superconductor induced the additional Bi-2212 phase with increasing RE concentration. The crystallographic structures of the samples were slightly changed from tetragonal to orthorhombic in higher concentration of x> 0.000, x > 0.100 and x> 0.025 for the Eu, Dy and Yb samples, respectively. Consequently, the analyses showed a decrease of the lattice parameter c and volume fraction for the Bi-2223 phase with the substituted sample while the SEM investigations showed that the surface morphology of microstructures had degraded, the grain connectivity became weak and the porosity increased with RE concentration. This resulted in the degradation of superconducting properties and it exhibited less grain alignment and connectivity that resulted in the decline of Jc with RE substitution. However, Yb showed better grain alignment compared to the Eu and Dy substituted samples. TOA results showed identical thermal behaviour for each substitution samples, which underwent different stages during their formation. TO analyses showed that there were five steps of mass loss for precipitated powder. TO curve for the sample x = 0.025 Eu, Dy and Vb, which has been calcined for 24 hours at 845°C shows only one drop in temperature above 800°C. Apparently, no indication of mass loss could be seen below -800°C. Therefore, it revealed that the formation of the carbonate can be suppressed in the calcined stage. FTIR results showed that the apparent infrared spectrum on all the precursor powders qualitatively showed four main regions and the existence of -OH group has an ability to increase the diffusion rate between metals during synthesis process. Increasing the concentration of Eu, Dy and Yb substituted in the Bi-2223 caused the decrement of Jc and Tc values. Jc and Tczero of the substituted samples were found to be lower than for the pure sample with almost the same Tc zero; however, the Yb substitution showed greater Jc with 4.1910 A/cm2 compared with the other substitutions.